Morphological Studies Of Dhsa/Dhsa-Octyl Ester/Rbd Palm Kernel Olein/Medium Chain Triglycerides System - Kassim, Anuar; Rathidevi, Nadarajan; Ismail, Zahariah; Desa, Mohd Zaizi; Mohd Sharif, Atan; Kuang, Dzulkefly; Haron, Md Jelas (Malaysian Society of Analytical Sciences, 2007)
Dihydroxystearic acid (DHSA) and octyl dihydroxystearate (DHSA-octyl ester) have been previously prepared from palm oleic acid and preliminary results showed that these compounds are suitable in personal care and cosmetics products. The objective of this research is to study the phase behavior in ternary system of DHSA/DHSA-octyl ester/RBD Palm Kernel Olein (RBDPKOo) & MCT at 85oC. From the ternary phase diagram, results showed that all ratios of were completely in two-phase region with various concentrations of RBDPKOo and MCT. The phase changes were observed through polarizing light while the formation of texture was confirmed using polarizing microscope combination with heating. Needles and spherulite textures were found in this system.